Increased Excitability and Reduced Excitatory Synaptic Input Into Fast-Spiking CA2 Interneurons After Enzymatic Attenuation of Extracellular Matrix - Hayani, Hussam; Song, Inseon; Dityatev, Alexander (Frontiers in Cellular Neuroscience, 2018)
The neural extracellular matrix (ECM) is enriched with hyaluronic acid, chondroitin sulfate proteoglycans (CSPGs), and the glycoprotein tenascin-R, which play important roles in synaptic plasticity, as shown by studies of the CA1 region of the hippocampus. However, ECM molecules are strongly expressed in the CA2 region, which harbors a high number of fast-spiking interneurons (FSIs) surrounded by a particularly condensed form of ECM, perineuronal nets. Despite this intriguing peculiarity, the functional role of ECM in the CA2 region is mostly unknown. Here, we investigate the acute and delayed effects of chondroitinase ABC (ChABC), an enzyme that digests chondroitin sulfate side chains of CSPGs and greatly attenuates neural ECM, on neuronal excitability and excitatory transmission in the CA2 region. Whole-cell patch clamp recordings of CA2 pyramidal cells (PCs) and FSIs in hippocampal slices revealed that seven days after injection of ChABC into the CA2 region in vivo, there are alterations in excitability of FSIs and PCs. FSIs generated action potentials with larger amplitudes and longer durations in response to less depolarizing currents compared to controls. PCs were excited at less depolarized membrane potentials, resulted in lower latency of spike generation. The frequency of excitatory postsynaptic currents in FSIs was selectively reduced, while the frequency of inhibitory postsynaptic currents was selectively increased. Acute treatment of hippocampal slices with ChABC did not result in any of these effects. This increase in excitability and changes in synaptic inputs to FSIs after attenuation of ECM suggests a crucial role for perineuronal nets associated with FSIs in regulation of synaptic and electrical properties of these cells.